Perceived organizational support on affective commitment with organization-based self-esteem as a mediating variabel - Amia, Refsi Amia; Syahrizal, Syahrizal (Human Resource Management Studies, 2023)
This study's objective was to analyze the relationship between perceived organizational support, and affective commitment when organization-based self-esteem is a mediating variabel to employee PT Umega Sembilan Berlian Dharmasraya. All employees of PT Umega Sembilan Berlian Dharmasraya were included in this study, totaling 153 employees. 111 employees were selected from the sample using the simple random sampling method in the study. This study is a type of descriptive causative research. Using SmartPLS 4, the Structural Equational Model (SEM) was used as the data analysis method. This study’s findings revealed that: (1) Perceived organizational support has a significant influence on affective commitment. (2) Peceived organizational support has a significant influence on organization-based self-esteem. (3) Organization-based self-esteem has a significant influence on affective commitment. (4) Organization-based self-esteem mediating the perceived organizational support and affective commitment to employees at PT Umega Sembilan Berlian Dharmasraya.